FEASIBILITY OF PRACTICUM-BASED E-SAS LIVEWORKSHEET TO IMPROVE CRITICAL THINKING SKILLS - Devlyn Angelia Hariono; Rusmini (Universitas Negeri Surabaya, 2026)
This study aims to develop a laboratory-based E-SAS liveworksheet that is suitable for use as teaching material to train critical thinking skills in reaction rate material based on three aspects, namely validity, practicality, and effectiveness. This study uses an R&D research type with a 4D model limited to the develop stage. A limited trial was conducted in the 11th grade at a private high school in Surabaya with 30 students. The results showed that the content validity and construct validity of the practical-based E-SAS liveworksheet for training critical thinking skills in reaction rate material met the validity criteria, as indicated by a content criterion mode of 5 in the very good category and a construct of 4 in the good category. The practicality of the E-SAS liveworksheet based on practical work to train critical thinking skills in reaction rate material was declared practical based on the results of the average student response questionnaire of 97% and supported by the results of student activity observations with a mode of 5 in the very good category. The E-SAS liveworksheet based on practical work to train critical thinking skills in reaction rate material was declared effective based on the results of the paired sample t-test with a p-value of 0.000, p-value <0.05, which means that there was a significant difference between the pretest and posttest of students' critical thinking abilities.